2020
DOI: 10.3348/kjr.2019.0739
|View full text |Cite
|
Sign up to set email alerts
|

Use of Magnetic Resonance Neurography for Evaluating the Distribution and Patterns of Chronic Inflammatory Demyelinating Polyneuropathy

Abstract: Objective: To evaluate the distribution and characteristics of peripheral nerve abnormalities in chronic inflammatory demyelinating polyneuropathy (CIDP) using magnetic resonance neurography (MRN) and to examine the diagnostic efficiency. Materials and Methods: Thirty-one CIDP patients and 21 controls underwent MR scans. Three-dimensional sampling perfections with application-optimized contrasts using different flip-angle evolutions and T1-/T2-weighted turbo spinecho sequences were performed for neurography of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
(40 reference statements)
3
11
0
Order By: Relevance
“…We found diffuse uniform hypertrophy of the brachial plexus, and multifocal fusiform hypertrophy of the LS plexus. The thickened pattern was similar to that of CIDP ( Su et al, 2020 ). The inherent mechanism should be evaluated further.…”
Section: Discussionsupporting
confidence: 71%
“…We found diffuse uniform hypertrophy of the brachial plexus, and multifocal fusiform hypertrophy of the LS plexus. The thickened pattern was similar to that of CIDP ( Su et al, 2020 ). The inherent mechanism should be evaluated further.…”
Section: Discussionsupporting
confidence: 71%
“… 9 However, the presence of enhancement may not be useful in distinguishing between POEMS and CIDP, because it can also be observed in the latter group of patients. 12 14 Interestingly, it serves as a potential marker for detecting disease activity or treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…The typical distribution of CIDP has been determined using MR Neurography in multiple studies, found to frequently involve the bilateral extracranial vagus, trigeminal, and intercostal nerves. The distribution of hypertrophy is typically uniform and bilateral [ 4 , 5 ]. The nerve roots, diffusely, are also known to hypertrophy in this disease.…”
Section: Typical Distribution Of Diseasementioning
confidence: 99%
“…The nerve roots, diffusely, are also known to hypertrophy in this disease. Other distributions, such as multifocal fusiform hypertrophy or unilateral involvement of the nerves may be seen in variant cases and atypical demonstrations of CIDP [ 4 , 5 ]. A 2003 case study presented a patient enduring a 10-year history of CIDP, with intercostal nerve enlargement in addition to brachial plexus and nerve root involvement illustrating the typical, expected distribution of disease [6] .…”
Section: Typical Distribution Of Diseasementioning
confidence: 99%
See 1 more Smart Citation